Design of Application for Payment of Education fees in the Junior High School of Taruna Nusa Harapan Mojokerto - Pratama, Benediktus Danny; Sutanto, Teguh; Binawati, Lilis (Jurnal Sistem Informasi Universitas Dinamika, 2021)
Abstract: Taruna Nusa Harapan Junior High School Mojokerto is a national private school and one of the schools under the Foundation Education Taruna Nusa Harapan. Education funding in TNH Junior high school obtained independently from parents/guardians of learners. There are four DP groups (development Fund) and SPP (contribution of Education) that is based on the income of the student's parents/guardians and is supported by the electricity bill proof. The determination of the group is based on a foundation policy benchmark that practice the determination of the group is a difference by the manager who is one with the other. In addition, all tuition costs ranging from PPDB, DP, SPP, DU and other costs, the record is less regular, so it often loses the evidence of payment and there is a mistake between learners who have paid and who have not paid. In addition to the time of creating a recapitulation report, the TU Finance Section checks one by one student data that has not been paid per class, so that it takes a long time.Based on the problem it takes an application that can set the right group, help the Finance section to do the recording, look for the students ' data that has not been paid for SPP payments can be easier to produce the recapitulation of SPP payment and other fees.As a result of a trial conducted in TNH Junior High School, this application can be used to classify DP and SPP, Meba student Data Report, proof of pay report, PPDB Payment Report, SPP Payment report, other expense report, Recapitulation report, Keywords : TNH Junior high school, learners, admissions new learners, development funds, contributions education organization, re-register